Functional and postoperative outcomes after high-intensity interval training in lung cancer patients: A systematic review and meta-analysis - Chen, Zihao; Jia, Junqiang; Gui, Dongmei; Liu, Feng; Li, Jun; Tu, Jiayuan (Frontiers in Oncology, 2023)
Objective: To evaluate the effects of high-intensity interval training (HIIT) on postoperative complications and lung function in patients with lung cancer compared to usual care. Method: We searched electronic databases in April 2022, including PubMed, Embase, Cochrane Library, Web of Science, and China National Knowledge Infrastructure (CNKI). Two authors independently applied the Cochrane Risk of Bias tool to assess the quality of RCTs. The postoperative complications, length of hospitalization, and cardiopulmonary functions from studies were pooled for statistical analysis. Results: 12 randomized controlled trials were eligible for inclusion and conducted in the meta-analysis. HIIT significantly increased VO2peak (MD = 2.65; 95% CI = 1.70 to 3.60; I2 = 40%; P < 0.001) and FEV1 (MD = 0.12; 95% CI = 0.04 to 0.20; I2 = 51%; P =0.003) compared with usual care. A subgroup analysis of studies that applied HIIT perioperatively showed significant improvement of HIIT on FEV1 (MD = 0.14; 95% CI = 0.08 to 0.20; I2 = 36%; P < 0.0001). HIIT significantly reduced the incidence of postoperative atelectasis in lung cancer patients compared to usual care (RD = -0.16; 95% CI = -0.24 to -0.08; I2 = 24%; P < 0.0001). There was no statistically significant effect of HIIT on postoperative arrhythmias (RD = -0.05; 95% CI = -0.13 to 0.03; I2 = 40%; P = 0.22), length of hospitalization (MD = -1.64; 95% CI = -3.29 to 0.01; P = 0.05), and six-minute walk test (MD = 19.77; 95% CI = -15.25 to 54.80; P = 0.27) in comparison to usual care. Conclusion: HIIT may enhance VO2peak and FEV1 in lung cancer patients and reduce the incidence of postoperative atelectasis. However, HIIT may not reduce the incidence of postoperative arrhythmia, shorten the length of hospitalization and improve the exercise performance of patients with lung cancer.